Safety and efficacy revisited: a systematic review and meta-analysis of glue versus tack mesh fixation in laparoscopic inguinal herniorrhaphy - Raja, Sandesh; Raja, Adarsh; Ansari, Ziyan; Eman, Sara; Bajaj, Simran; Ahmed, Muhammad; Kumar, Uday; Shah, Yawar Hussain; Jawahar, Sachin; Aftab, Faisal; Rajani, Deepak; Kumar, Satesh; et al. (Frontiers in Surgery, 2024)
Background This analysis addresses the uncertainty surrounding the efficacy of glue mesh fixation (GMF) compared with tack mesh fixation (TMF) in laparoscopic herniorrhaphy. Our meta-analysis incorporates recently conducted randomized controlled trials (RCTs) to enhance the reference for assessing the efficacy and safety of GMF. Methods PubMed Central, Google Scholar, Science Direct, and Cochrane Library were extensively reviewed for articles in the English language performed from inception to May 2023 using the keywords “Glue mesh repair,” “Tack mesh repair,” “Inguinal Hernia,” “Herniorrhaphy,” “Laparoscopic,” “Mesh Fixation,” and “Randomized controlled trials.” Results In this meta-analysis, we incorporated a total of 20 randomized controlled trials, evaluating each article individually using quality ratings. Compared with TMF, GMF demonstrated a significant reduction in the incidence of chronic pain [RR: 0.40, (0.23, 0.68)] and pain scores on postoperative day 1 [MD: −1.07, (−1.90, −0.25)]. We also used funnel plots and Egger's regression to test for publication bias. Conclusion In summary, this meta-analysis establishes the significance of GMF in reducing chronic pain and postoperative day 1 pain compared with TMF. However, no statistically significant difference was noted between the GMF and TMF groups concerning hematoma, seroma, operation time, recurrence rate, and total complications. Nonetheless, given the small number of cases in this study, the findings must be validated in the future by multicenter, large-sample, high-quality RCTs.